2016
DOI: 10.3390/vaccines4030032
|View full text |Cite
|
Sign up to set email alerts
|

Ag85A DNA Vaccine Delivery by Nanoparticles: Influence of the Formulation Characteristics on Immune Responses

Abstract: The influence of DNA vaccine formulations on immune responses in combination with adjuvants was investigated with the aim to increase cell-mediated immunity against plasmid DNA (pDNA) encoding Mycobacterium tuberculosis antigen 85A. Different ratios of pDNA with cationic trimethyl chitosan (TMC) nanoparticles were characterized for their morphology and physicochemical characteristics (size, zeta potential, loading efficiency and pDNA release profile) applied in vitro for cellular uptake studies and in vivo, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 33 publications
0
20
1
Order By: Relevance
“…Preclinical studies by different research groups have successfully demonstrated the efficacy of NP based vaccines in the induction of specific immune responses against tuberculosis ( 42 , 179 182 ). Feng et al developed a NP-based recombinant DNA vaccine that consists of Esat-6 and fms-like tyrosine kinase 3 ligand enveloped with chitosan NPs ( 42 ).…”
Section: Implications Of the Nanocarriers In The Vaccine Developmentmentioning
confidence: 99%
“…Preclinical studies by different research groups have successfully demonstrated the efficacy of NP based vaccines in the induction of specific immune responses against tuberculosis ( 42 , 179 182 ). Feng et al developed a NP-based recombinant DNA vaccine that consists of Esat-6 and fms-like tyrosine kinase 3 ligand enveloped with chitosan NPs ( 42 ).…”
Section: Implications Of the Nanocarriers In The Vaccine Developmentmentioning
confidence: 99%
“…Reorganized Ag85A DNA was demonstrated to trigger strong immune reactions, leading to dramatic upregulation of Th1 cytokines (IFN-γ and IL-2), which are crucial mediators of immunity. In turn, the Th1 cytokines functioned by stimulating cytotoxic cells and eliminating infected cells ( 36 38 ). In the current study, it was observed that Ag85A-DCs promoted allogeneic T-cell proliferation and increased IFN-γ production.…”
Section: Discussionmentioning
confidence: 99%
“…82 Intramuscular immunization with pDNA encoding antigen 85A of M. tuberculosis provoked a significant Th1 response in mice. 83 Many routes have been explored for TMC vaccination. However, there is scope for further intervention into new routes.…”
Section: Route Of Administrationmentioning
confidence: 99%